Le cas Coursera ou la préfiguration des changements en cours sur les plateformes d'apprentissage en ligne - François Acquatella; Valérie Fernandez; Thomas Houy (Centre National d'Enseignement à Distance, 2018)
The development of digital platforms reflects a renewal of the economic paradigm. This article aims to suggest a new conceptual framework by presenting a view of the main disruptive strategic trajectories implemented a new type of platform. In a second time it aims to contribute to the understanding of the dynamics of platform strategy through the analysis of the case of Coursera. The iterations of this platform with a market under construction can be read as a strategy to bring out new proposals and value networks. Finally, we discuss the « drivers » of future changes in the MOOC market.